2018
DOI: 10.1016/j.euo.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Comorbidity and Competing-risks Assessments for Bladder Cancer Patients

Abstract: Context Radical cystectomy continues to be associated with a significant risk of morbidity and all-cause mortality (ACM). Practice pattern data demonstrating underuse of surgery for patients with muscle-invasive and high-risk non–muscle invasive bladder cancer (BC) have been linked to the advanced age and higher comorbidity status of such patients, which suggests that rates of ACM as well as cancer-specific mortality should be incorporated into patient counseling and guideline recommendations. Objective To r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 66 publications
2
30
0
Order By: Relevance
“…However, male patients were still at higher risk of OCM than females. In consequence, unmarried and male patients may represent prime targets for preventative measures aimed at OCM risk reduction, along with the elderly patients 20‐24 …”
Section: Discussionmentioning
confidence: 99%
“…However, male patients were still at higher risk of OCM than females. In consequence, unmarried and male patients may represent prime targets for preventative measures aimed at OCM risk reduction, along with the elderly patients 20‐24 …”
Section: Discussionmentioning
confidence: 99%
“…There exists surplus of studies which pertain to the comorbidity index to be used in the prediction of the OS in the follow up in the long term and the perioperative mortality of 90 days for the patients on which radical cystectomy is planned due to bladder tumors (4,12,13,14). Different studies have shown that the elder age, angina pectoris, smoking history, chronic lung diseases and Diabetes Mellitus were used as independent prognostic factors to predict the 10-year mortality subsequent to cystectomy (13,15). However, instead of evaluating the comorbid conditions individually, it is thought to be more valuable to use nomograms that examine the total morbidity burden (2).…”
Section: Discussionmentioning
confidence: 99%
“…According to the updated guidelines of the European Association of Urology (EAU), it is suggested to make an evaluation for the morbidity of the potential patients who are to undergo radical cystectomy preoperatively (3). For this purpose, the widely used scoring systems are ACCI and ASA and it has been observed that they are much more beneficial for the prediction of the complications which may develop in the elder patients during the first 30 days after the operation and the cancer free mortality in the first 90 days (13,14). It has been reported that the prognostic value of ACCI may be higher in the estimation of five-year mortality due to all causes (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comorbidity is an important risk factor for periop- erative and long-term mortality after radical cystectomy. There is, however, no consensus on the best way to measure it in this setting [3,4].…”
Section: Introductionmentioning
confidence: 99%